Macroeconomic developments and policies since 2000 - Shankar N. Acharya (Indian Council for Research on International Economic Relations (ICRIER), 2025)
The first section provides a brief review of developments in key macroeconomic variables since 2000. These include the usual target variables of economic growth, inflation, external balance and employment as well as intermediate target variables of fiscal balance, savings and investment. Section II considers some of the major exogenous shocks experienced in the last 24 years and how well (or badly) India's policies coped with them. The shocks include the foreign capital surge of 2006-8, the global financial crisis (GFC) of 2008-9 and the Covid pandemic that hit India in 2020. Section III considers some of the key macro challenges that lie ahead. These include; the worsened international economic environment produced by undermining of the rules- based, liberal, world trading order by the first four months of second Trump administration in the US through steep tariffs on major trading partners (China, EU, Canada and Mexico) as well as higher tariffs on nearly all other trading nations; the need to raise India's aggregate investment, savings and exports through an array of economic policy reforms in foreign trade, factor markets, taxation and deregulation to raise the rate of economic growth from 6-6.5 percent to above 8 percent; and ensure a more employment-intensive pattern of development, while maintaining external and domestic macro balance.
Keywords: E2; E6; F4; H3; H6; 330; India; Macroeconomic Policy; Economic Growth; Inflation; Employment; External Balance; Fiscal Deficits and Debt; Savings and Investment